2002
DOI: 10.1108/03699420210442301
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study in emulsion polymerization of polyurethane‐acrylate hybrids

Abstract: Polyurethane (PU) anionomer having 2‐ethoxymethacrylate terminal groups was prepared in a methyl methacrylate/n‐butyl acrylate mixture as a reactive diluent, following a prepolymer mixing process. This prepolymer‐acrylic monomer mixture was chain extended in a water/surfactant solution using different dispersion speeds. Stability tests of PU‐acrylic monomer dispersions before polymerization were performed at different temperatures by following the particle size evolution. After the dispersion process the kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…PU/acrylic hybrid dispersions are attractive because the (meth)­acrylic polymers are resistant to water and alkalis, and in addition they come at lower costs. These hybrid dispersions can be prepared by using PUDs synthesized as outlined above as the seed in a seeded semicontinuous emulsion polymerization of acrylic monomers. Alternatively, the NCO-terminated PU prepolymer prepared in solution is isolated, dissolved in (meth)­acrylic monomers, and dispersed in water using high shear forces such as ultrasound (for lab-scale) or high-pressure homogenization. The acrylic monomers are subsequently polymerized via miniemulsion polymerization, and the PU can be chain-extended in the dispersed phase prior to or after polymerization. ,, However, miniemulsification may be a bottleneck in large-scale processes .…”
Section: Introductionmentioning
confidence: 99%
“…PU/acrylic hybrid dispersions are attractive because the (meth)­acrylic polymers are resistant to water and alkalis, and in addition they come at lower costs. These hybrid dispersions can be prepared by using PUDs synthesized as outlined above as the seed in a seeded semicontinuous emulsion polymerization of acrylic monomers. Alternatively, the NCO-terminated PU prepolymer prepared in solution is isolated, dissolved in (meth)­acrylic monomers, and dispersed in water using high shear forces such as ultrasound (for lab-scale) or high-pressure homogenization. The acrylic monomers are subsequently polymerized via miniemulsion polymerization, and the PU can be chain-extended in the dispersed phase prior to or after polymerization. ,, However, miniemulsification may be a bottleneck in large-scale processes .…”
Section: Introductionmentioning
confidence: 99%
“…The use of a functional monomer that can introduce double bonds in the PU chains that subsequently can participate in the free‐radical polymerization of (meth)acrylics offers a way to produce grafted hybrids and improve the compatibility between PU and (meth)acrylics . Functional monomers containing both hydroxyl and (meth)acrylic groups are interesting because this dual functionality allows the monomers to react with the isocyanate groups during the formation of the polyurethane and with radicals during the formation of the poly(meth)acrylic chains.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we examined the kinetic reactions of these systems,22 and we reported the characterization of samples where the acrylic content was varied from 0 to 50 wt %. Higher amounts of acrylic components led to coagulation, and no film‐forming systems were obtained 23.…”
Section: Introductionmentioning
confidence: 99%